2011
DOI: 10.1038/cddis.2011.82
|View full text |Cite
|
Sign up to set email alerts
|

CYLD regulates keratinocyte differentiation and skin cancer progression in humans

Abstract: CYLD is a gene mutated in familial cylindromatosis and related diseases, leading to the development of skin appendages tumors. Although the deubiquitinase CYLD is a skin tumor suppressor, its role in skin physiology is unknown. Using skin organotypic cultures as experimental model to mimic human skin, we have found that CYLD acts as a regulator of epidermal differentiation in humans through the JNK signaling pathway. We have determined the requirement of CYLD for the maintenance of epidermal polarity, keratino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 29 publications
7
47
0
Order By: Relevance
“…We have analyzed by smooth muscle actin immunostaining the pattern of blood vessels in both C57-Control-metastasis and CYLD C/S -metastasis and found that C57-CYLD C/S -metastases were highly vascularized (Figure 3h), whereas we hardly detected smooth muscle actinpositive staining in the C57-Control-metastasis (Figure 3g). This result is in agreement with our previous finding showing an enhanced angiogenesis in the skin tumors obtained by subcutaneous inoculation of both the murine C57 and human A431 SCC cells expressing the CYLD C/S mutant (Alameda et al, 2010(Alameda et al, , 2011a.…”
Section: C57-cyld C/s -Metastases Show Markers Distinctive Of Highly supporting
confidence: 93%
See 4 more Smart Citations
“…We have analyzed by smooth muscle actin immunostaining the pattern of blood vessels in both C57-Control-metastasis and CYLD C/S -metastasis and found that C57-CYLD C/S -metastases were highly vascularized (Figure 3h), whereas we hardly detected smooth muscle actinpositive staining in the C57-Control-metastasis (Figure 3g). This result is in agreement with our previous finding showing an enhanced angiogenesis in the skin tumors obtained by subcutaneous inoculation of both the murine C57 and human A431 SCC cells expressing the CYLD C/S mutant (Alameda et al, 2010(Alameda et al, , 2011a.…”
Section: C57-cyld C/s -Metastases Show Markers Distinctive Of Highly supporting
confidence: 93%
“…This mutant carries the 601 C/S point mutation in the cysteine box of the deubiquitinase domain, resulting in a catalitically inactive protein that is able to compete with the endogenous CYLD. We found that the expression of the CYLD C/S mutant makes the squamous cancer PDVC57 cells (SCC cells) very aggressive, conferring them properties such as capacity of growing in suspension and increased angiogenesis that finally leads to a rapid tumor development in carcinogenesis assays (Alameda et al, 2010(Alameda et al, , 2011a. Now we have performed in vivo metastasis assays to ascertain whether CYLD has a role in the metastatic behavior of SCC epidermal cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations